Young Adults and Labor Markets in Africa - Oriana Bandiera; Ahmed Elsayed; Andrea Smurra; Celine Zipfel (Institute of Labor Economics (IZA), 2021)
Every year millions of young adults join the labor market in Africa. This paper uses the Jobs of the World Database to compare their job prospects to those of their counterparts in other low-income regions. We show that employment rates are similar at similar levels of development but young adults in Africa are less likely to have a salaried job, especially when the size of their cohort is large. Building on existing evidence on the impacts of interventions targeting both the demand and supply sides of the labor market, we discuss policy priorities for boosting the growth of salaried job creation in the region.
Keywords: J01; J08; J21; J24; 330; young adults; employment; salaried jobs; Africa